Architecture, Resilience and the Articulation of Urban Dilemmas - Singh, Rahoul (International Planning History Society Proceedings, 2016)
ABSTRACT This paper views the City as the product of a complex web of ongoing social and cultural developments. It bases its understanding on the premise that a City and its landscapes, act as agents of historic transmission and documentation that are bound together by the varying degrees of elasticity embodied within them. It proposes that when an engagement with the past happens through the insertion of catalytic programs posited against the historic artifact it creates an episodic urbanism. Collectively viewed these, “episodes” which place the individual at the center of a negotiated urban experience pushes the elastic limits of a city’s resilience and hence acts as both an agent for continuity and change. Architecture, Palimpsest, Resilience, Thirdspace Urbanism, Urban Episodes